Potential Impact of the Free Trade Area of the Americas on the U.S. Sugarcane Industry - José Alvarez (EDIS)
Countries and regions are moving to liberalize trade throughout the world. Many bilateral and multilateral agreements have been signed in the past few years and others are under negotiation. The Free Trade Area of the Americas (FTAA) is currently being negotiated. As in every trade agreement, the FTAA is likely to produce winners and losers. The U.S. sugar industry appears to be among the losers. The objective of this fact sheet is to describe the general characteristics of the FTAA and explore its potential negative impacts on the U.S. sugar industry. This is EDIS document FE563, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published June 2005.